Promoting sustainable responses to the US opioid epidemic with community-academic partnerships: qualitative outcomes from a statewide program - David L.Driscoll; Alison Evans Cuellar; Vinod Agarwal; Debra Jones; Mary Beth Dunkenberger; Kathy Hosig (BMC, 2022)
Abstract Background Drug overdose deaths in the United States have continued to increase at an alarming rate. The Substance Abuse and Mental Health Services Administration (SAMHSA) distributed more than $7 billion between January 2016 and June 2020 to address the drug overdose crisis. The funds support evidence-based responses, including medications for opioid use disorder, and other prevention, treatment and recovery activities. Although the State Opioid Response (SOR) grants finance much-needed community level interventions, many of the services they support may not be sustainable, without ongoing assessment, evaluation and planning for continuation. Methods This paper describes a statewide effort to support local entities through SAMHSA's SOR grants in Virginia. Community agencies across the state participated in detailed needs assessment exercises with VHEOC investigators, and developed requests for proposals (RFPs) to sustain their SOR programs. The RFPs were then distributed to prospective academic partners at the five VHEOC universities, based on the required subject matter expertise identified in the RFP. All responsive proposals were then provided to the local agencies who selected the proposal most likely to meet their needs. VHEOC investigators also conducted an inductive, three-phase content analysis approach to examine the RFPs submitted to the VHEOC to identify nominal categories of support requested of the VHEOC investigators. Results VHEOC Investigators received and coded 27 RFPs from ten community agencies representing four of five regions of the state. We identified six nominal categories of academic assistance with high inter-coder agreement. The six categories of support requested of the academic partners were program development and support, literature review and best practices, outreach and education, data analysis and interpretation, program evaluation, and grant writing assistance. Several RFPs requested up to three categories of support in a single project. Conclusions Our analysis of the requests received by the consortium identified several categories of academic support for SOR-grantees addressing the drug overdose crisis. The most common requests related to development and maintenance of supportive collaborations, which existing research has demonstrated is necessary for the long-term sustainability of SOR-funded services. In this way, the academic partners reinforced sustainable SOR-funded programs. As the state opioid response program is implemented nationally, we hope that other states will consider similar models in response to the opioid crisis.